EDUCATIONAL DYNAMICS WITH THE NURSING STAFF UNDER A CULTURAL CARE FOCUS ON MOTHERS AT PUERPERIUM - Vanessa Munhoz de Oliveira Krüger; Ivete l Palmira Sanson Zagonel (Universidade Federal do Paraná, 2002)
This study was held in a hospital in Curitiba in order to reorient actions under a cultural care focus on mothers and their newly-born babies. The theoretical background was founded on the ideas as well as some concepts of Madeleine Leininger's Cultural Care Universality and Diversity Theory in order to reach this goal. The work was effected through meetings and educational health dynamics. They aimed to promote individual and group values and help nursing professionals' education towards the development of their initiative, organization skills, liveliness, comunicability, leadership, creativity, health education and cultural care effectiveness. It was possible to evidence, from the staff accounts, the impact of educational health dynamics, proving the relevance of the cultural focus on the quality of the nursing care provided to mothers at puerperium and their babies. It was also evidenced the importance of team work which brings about the team union, motivation and improvement on professional intergroup performance.